If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -27 = 15 + 4x Reorder the terms: -27 + x = 15 + 4x Solving -27 + x = 15 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -27 + x + -4x = 15 + 4x + -4x Combine like terms: x + -4x = -3x -27 + -3x = 15 + 4x + -4x Combine like terms: 4x + -4x = 0 -27 + -3x = 15 + 0 -27 + -3x = 15 Add '27' to each side of the equation. -27 + 27 + -3x = 15 + 27 Combine like terms: -27 + 27 = 0 0 + -3x = 15 + 27 -3x = 15 + 27 Combine like terms: 15 + 27 = 42 -3x = 42 Divide each side by '-3'. x = -14 Simplifying x = -14
| (5x^3-24x^2+15x+4)/(x-4) | | 3(t-1)=9 | | xm+6=-2 | | 11n-3-5n+7= | | x/3-4=17 | | -5=+-11 | | 12x+13=5x+139 | | 34(7-2.5x)=14(2x-10)+61.6 | | -5=t-11 | | 2[s+3(a-1)]=18 | | 3/8(4a-5)-5/12(3a-4)=1/6 | | 25=1+5x-x | | 8x^2+47x+28= | | (-2)(x)=3x | | 3p+8=1-2p+4p | | 22=-6f+8 | | 4x^-1y^-1/-4x^2 | | x+0=4 | | 10+6g=-20 | | X^4-4x^3+2x^2-8x=0 | | 36(47-5.5x)=16(5x-9)+84.6 | | 6v-9=v | | (3x^2)-7x-4=2 | | -5x-10=0equation | | 8/32+5/8=13/16 | | -1/-8x=5/24 | | -1/8x=5/24 | | 2x-6/4=4x-3 | | 5x+32=14x+67 | | (3z-u)*(3z+5u)= | | 0.9p^2-8p+3.3=2 | | 2x-6=4x-3 |